Incidence and mortality of cutaneous lymphoma in North-Rhine Westphalia/Germany: recent trends and data of the population-based cancer registry of North Rhine Westphalia. (October 2021) - El Najjarine, Khodr Cheikh; Kajüter, Hiltraud; Wellmann, Ina; Stang, Andreas; Assaf, Chalid
Abstract : Primary cutaneous lymphoma (CL) form a heterogenous group of non-Hodgkin lymphoma (NHL). The CL are divided into T cell lymphoma (CTCL), these form the majority of CL with 73%, followed by B cell lymphoma (CBCL) with 22% and the rare lymphoma build 5% based on the current WHO-classification. There are only few studies, which treated the CL topic and its incidence, prevalence and survival in Germany. The last study has been published in the year 2007 including 998 patients from 26 different centers. However, recent studies from other national registries show a slight increasing tendency of incidence and prevalence of CL. Therefore, the underlying study investigated aged-standardized incidence rates and 5-year survival of CL for the time period 2008–2017 with data of the population-based cancer registry (LKR) of North Rhine-Westphalia, the largest Federal State of Germany (18 million inhabitants). Overall, 2826 patients with CL were registered in the period of 2008 till 2017 of the cancer registry. The LKR is a reporting point of all forms of cancer, based on an obligated report for all pathologists and dermatopathologists since 2005. The data is allocated as followed 1743 male (61.7%) and 1083 female (38.3%) with a rate of male>female (1.6:1). The present work shows based on the registration of 2826 patients the dominance of cutaneous T-cell-lymphoma (68%) in comparison to cutaneous B-cell-Lymphoma (24.9%), however we also divided the primary cutaneous B cell lymphoma (CBCL) in one overall category (n=905) and three subtypes (n=705): follicular B cell lymphoma (C82), diffuse large B cell lymphoma (C83.3) and marginal zone lymphoma; C88.40), with the following distribution 37.7%, 30.2%, 32.1%. The age-standardized incidence rates (per 100 000 person-years) of cutaneous lymphoma were 1, 5 and 0, 8 among men and women. Five-year absolute survival was 79.1% in MF, and 77.3% in all CBCL and 88.2% in marginal zone lymphoma, 89.6% in follicular lymphoma and 49.6% in diffuse large B cell lymphoma, respectively. Overall, there is a stable incidence in CTCL and a slightly increasing incidence of CBCL (0.14 in 2008 to 0.34 in 2017). This progression in CBCL may be due to higher awareness and clear substratification based on the recent classifications.